Analysis of the Damage of Rigid Pavement Road by Using Pavement Condition Index (PCI) - Isradi, Muhammad; Arifin, Zaenal; Sudrajat, Asep (Yayasan Ahmar Cendekia Indonesia, 2019)
Bogasari Road, which is located in Citeureup sub-district, Bogor Regency, within the PT Indocement Tunggal Prakarsa industrial area, is a road that uses rigid pavement. The road is always passed by heavily loaded vehicles that affect road pavement conditions and the level of comfort and safety for road users. The study's purpose is to determine the average daily traffic volume, determine the value of conditions in the rigid pavement, and provide input to relevant agencies in terms of solutions and road repair costs. The method used in the analysis is the Pavement Condition Index (PCI). The study shows the average daily traffic of 2,883 vehicles/hour/day and the average pavement condition value of 66.57 with a good rating, or in good condition. It also provides a method of repair by functional means.